2023
DOI: 10.3390/ijerph20043516
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strength Training on Physical Fitness of Olympic Combat Sports Athletes: A Systematic Review

Abstract: This review aimed to identify the effects of strength training programs on the physical fitness of Olympic combat sports (OCS) athletes. The systematic review included peer-reviewed articles that incorporated interventions that included pre- and post-intervention physical fitness assessment. The search was performed in the SCOPUS, PubMed, and Web of Science databases between April and September 2022. PRISMA and the TESTEX checklist were used to select and assess the methodological quality of the studies. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…On the other hand, Guidetti, Musulin, and Baldari [ 10 ] reported mean HG strength values of 58.2 (6.9) kg in Italian boxers (22.3 [1.5] years; 1.77 [0.2] m; 77.4 [1.4] kg). It is important to highlight that a large contribution to PIF derives from lower limb muscle strength, as it has been shown that increases in power measured through vertical jumping are related to an increase in PIF [ 58 , 59 , 60 ]. This agrees with our findings since the profile with better functional performance (Cluster 2) had the highest records on PIF, the CMJ height and PV.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Guidetti, Musulin, and Baldari [ 10 ] reported mean HG strength values of 58.2 (6.9) kg in Italian boxers (22.3 [1.5] years; 1.77 [0.2] m; 77.4 [1.4] kg). It is important to highlight that a large contribution to PIF derives from lower limb muscle strength, as it has been shown that increases in power measured through vertical jumping are related to an increase in PIF [ 58 , 59 , 60 ]. This agrees with our findings since the profile with better functional performance (Cluster 2) had the highest records on PIF, the CMJ height and PV.…”
Section: Discussionmentioning
confidence: 99%
“…Basically, physical fitness is related to the quality of endurance (Gani et al, 2023), strength (Do Nascimento et al, 2023), power, speed, agility (Ben Hassen et al, 2022Kabadayı et al, 2022;Ojeda-Aravena et al, 2023), which should be gained by combat sports athletes. Data from previous studies reported that a prerequisite for achieving optimal results in combat sports is to improve physical fitness (Cid-Calfucura et al, 2023). Meanwhile, poor physical fitness could be a factor in reducing performance (Kudryavtsev et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the continuous progress of sports science and the new findings of research conducted in the field of sports has led to astonishing leaps in records and results obtained from sports activities; because knowledge of the structure and function of the body, both for maintaining health and improving sports performance, including important and attention-grabbing areas of study in physical education and sports science (Cid-Calfucura et al, 2023). Given the new conditions, to achieve excellence in any sport, we must first have comprehensive information about the physical conditions and body composition of athletes so that we can provide appropriate training programs for athletes to progress and advance to the desired levels by comparing this information with the status of elite athletes in that field.…”
Section: Introductionmentioning
confidence: 99%